2013
DOI: 10.2105/ajph.2012.301138
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Implementation of Policies to Support Preventive Dentistry Initiatives for Physicians: A National Survey of Medicaid Programs

Abstract: State Medicaid policies to reimburse nondental providers for preventive dental services are becoming widespread. Interventions are needed to ensure oral health services delivery at the practice level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Currently 46 state Medicaid programs reimburse physicians for some preventive dental services, most having adopted the policy since 2006. 31 Fluoride varnish, which is recommended by the American Academy of Pediatrics 32 and the US Preventive Services Task Force 33 for use by physicians beginning as soon as the first tooth erupts, is the procedure most commonly reimbursed. Studies of the North Carolina program found that Medicaid-enrolled children who have at least 4 IMBP visits by 3 years of age have a 17% lower rate of dental caries-related treatments by 6 years of age compared with children with no visits.…”
Section: Discussionmentioning
confidence: 99%
“…Currently 46 state Medicaid programs reimburse physicians for some preventive dental services, most having adopted the policy since 2006. 31 Fluoride varnish, which is recommended by the American Academy of Pediatrics 32 and the US Preventive Services Task Force 33 for use by physicians beginning as soon as the first tooth erupts, is the procedure most commonly reimbursed. Studies of the North Carolina program found that Medicaid-enrolled children who have at least 4 IMBP visits by 3 years of age have a 17% lower rate of dental caries-related treatments by 6 years of age compared with children with no visits.…”
Section: Discussionmentioning
confidence: 99%
“…43 The content and periodicity of POHS vary by state and some Medicaid programs reimburse POHS up to older ages. 12 Although most state Medicaid programs reimburse for fluoride varnish delivered in medical offices, 12 the practice is not common nationally. 13 Medicaid-enrolled kindergarten students included in our sample were found to have a high prevalence of untreated caries.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Several states reimburse physicians through their public insurance programs for dental screenings and oral health counseling, and almost all reimburse physicians for the application of fluoride varnish. 12,13 The literature suggests that physicians will adopt these services and provide quality care that is effective in increasing access to preventive services, reducing treatment needs, averting hospitalizations, and lowering Medicaid costs.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 By 2011, 42 states had adopted a policy to support preventive dentistry initiatives for physicians. 50 Two examples of these types of initiatives are discussed later.…”
Section: Expanding the Oral Health Teammentioning
confidence: 99%